CYTOGENETIC STUDIES ON FISHES OF THE FAMILY PIMELODIDAE (SILUROIDEI) - Dias, A. L.; Foresti, F. (Soc Brasil Genetica, 1993)
Four fish species of the family Pimelodidae were analyzed. Bergiaria westermani and two different Pimelodus species have the same diploid chromosome number (2n - 56). Despite some differences in chromosome structure, these species are highly similar in karyotype and differ from Pimelodella sp., which presents a reduction in chromosome number to 2n = 46. The data confirm the extensive chromosome variability existing in this family, characterized by intraindividual and/or population polymorphisms of a structural nature which may or may not be sexlinked, and by the presence of supernumerary chromosomes.